Asymmetries and Circumstellar Interaction in the Type II SN 2024bch - Jennifer E. Andrews; Manisha Shrestha; K. Azalee Bostroem; Yize Dong; Jeniveve Pearson; M. M. Fausnaugh; David J. Sand; S. Valenti; Aravind P. Ravi; Emily Hoang; Griffin Hosseinzadeh; Ilya Ilyin; et al. (The Astrophysical Journal)
We present a comprehensive multi-epoch photometric and spectroscopic study of SN 2024bch, a nearby (19.9 Mpc) Type II supernova (SN) with prominent early high-ionization emission lines. Optical spectra from 2.8 days after the estimated explosion reveal narrow lines of H i , He ii , C iv , and N iv that disappear by day 6. High-cadence photometry from the ground and Transiting Exoplanet Survey Satellite show that the SN brightened quickly and reached a peak M _V ~ −17.8 mag within a week of explosion, and late-time photometry suggests a ^56 Ni mass of 0.050 M _⊙ . High-resolution spectra from days 7.9 and 43 trace the unshocked circumstellar medium (CSM) and indicate a wind velocity of 30–40 km s ^−1 , a value consistent with a red supergiant (RSG) progenitor. Comparisons between models and the early spectra suggest a pre-SN mass-loss rate of $\dot{M}\,\unicode{x0007E}\,1{0}^{-3}\unicode{8210}1{0}^{-2}\,M_{\odot }\,{yr}^{-1}$ , which is too high to be explained by quiescent mass loss from RSGs, but is consistent with some recent measurements of similar SNe. Persistent blueshifted H i and [O i ] emission lines seen in the optical and near-IR spectra could be produced by asymmetries in the SN ejecta, while the multicomponent H α may indicate continued interaction with an asymmetric CSM well into the nebular phase. SN 2024bch provides another clue to the complex environments and mass-loss histories around massive stars.